The relative age effect in under-17, under-20, and adult elite female soccer players - Ribeiro, E.; Barreira, J.; Carraco, D.; Galatti, L.; Götze, M.; Abad, C. C. C. (Science and Medicine in Football, 2024)
To investigate the RAE in elite female soccer players, the absolute and relative birthdate distributions of players who disputed the Women`s World Cup were assessed. Differences between observed and expected distributions were analyzed using chi-square and effect sizes. The birthdates of 1224 female soccer players were assessed in Under-17 (N = 336), Under-20 (N = 336) and adult (N = 552) categories. There was no significant RAE in adult category for different playing positions and players in general (including all playing positions per age category). There was significant RAE for midfielders and players in general with mainly small effect sizes for the U-17 and U-20. In both age categories, players born in Q1 were over-represented with the highest quartile ratio for midfielders. In regard of RAE and success defined by final ranking at the World Cup, we found no significant differences between the birthdate distributions of players who participated in either the group stages or finally the knockout phases. Coaches should consider this information to avoid bias in talent programs designed to promote and select female soccer players independently of their birthdates. Young female players should be encouraged to learn to play in different field positions before to reach high-level performance.